Pulmonary Tuberculosis due to Mycobacterium bovis in Captive Siberian Tiger - Ákos Lantos; Stefan Niemann; László Mezősi; Endre Sós; Károly Erdélyi; Sándor Dávid; Linda M. Parsons; Tanja Kubica; Sabine Rüsch-Gerdes; Ákos Somoskövi (Emerging Infectious Diseases, 2003)
We report the first case of pulmonary tuberculosis caused by Mycobacterium bovis subsp. caprae in a captive Siberian tiger, an endangered feline. The pathogen was isolated from a tracheal aspirate obtained by bronchoscopy. This procedure provided a reliable in vivo diagnostic method in conjunction with conventional and molecular tests for the detection of mycobacteria.